2020
DOI: 10.1002/jmv.26441
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections and patterns of antibiotic use in patients with COVID‐19

Abstract: Introduction Bacterial coinfection is associated with poor outcomes in patients with viral pneumonia, but data on its role in the mortality of patients with COVID‐19 is limited. Methods This is a single‐center retrospective analysis of 242 patients with confirmed coronavirus disease 2019 (COVID‐19) admitted to both intensive care and non‐intensive care settings. Bacterial coinfection was determined by the presence of characteristic clinical features and positive culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
4
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 39 publications
10
73
4
4
Order By: Relevance
“…While our finding suggests that antibiotics does not improve patient outcomes, it is still possible that a higher prevalence of antibiotic administration in severe and critical patients could worsen inflammation. 42 Finally, gut microbiota composition is highly heterogeneous across human populations and changes in compositions reported here may not necessarily be reflected in patients with COVID-19 from other biogeographies. Nevertheless, this survey of gut microbiota alterations in association with immune dysregulation revealed that gut microorganisms are likely involved in the modulation of host inflammatory responses in COVID-19.…”
Section: Discussionmentioning
confidence: 81%
“…While our finding suggests that antibiotics does not improve patient outcomes, it is still possible that a higher prevalence of antibiotic administration in severe and critical patients could worsen inflammation. 42 Finally, gut microbiota composition is highly heterogeneous across human populations and changes in compositions reported here may not necessarily be reflected in patients with COVID-19 from other biogeographies. Nevertheless, this survey of gut microbiota alterations in association with immune dysregulation revealed that gut microorganisms are likely involved in the modulation of host inflammatory responses in COVID-19.…”
Section: Discussionmentioning
confidence: 81%
“…This finding suggests a direct clinical consequence of functional immunoparalysis in some patients with severe COVID-19 driven by high IL-10 blunting a pro-inflammatory antimicrobial response with low lymphocyte count impairing adaptive immunity. In general, secondary infections are associated with increased morbidity and mortality in viral respiratory infections, including COVID-19 [28][29][30]. In a comprehensive meta-analysis, Langford et al reported a prevalence rate of 14.3% (95%CI: 9.6-18.9%) for secondary bacterial infections in patients with COVID-19 [31].…”
Section: Discussionmentioning
confidence: 99%
“…Substantial differences occur in the clinical course of the disease, and the reasons for this variability are only partially known [ 15 , 16 ]. As a possible contributor, a deficient antibody response may be an important contributor to a more severe clinical course of the infection [ 17 ], as also suggested by the poorer prognosis in patients with bacterial co-infection [ 18 ]. The most serious clinical consequences are associated with male sex, older age, and the presence of co-morbidities, including obesity and diabetes [ 19 23 ].…”
Section: Introductionmentioning
confidence: 99%